Contributions of African Crops to American Culture and Beyond: The Slave Trade and Other Journeys of Resilient Peoples and Crops - Sousa, Emily C.; Raizada, Manish N. (Frontiers in Sustainable Food Systems, 2020)
There is a general unawareness of food crops indigenous to the African continent that have contributed to modern culture. This under-appreciation is particularly relevant in the current context of societal movements to end historic racism and value the contributions of peoples of African origin and African skin colours. Lack of awareness of the contributions of Africa’s crops has negative practical consequences, including inadequate investments in preserving and maximizing the use of crop diversity to facilitate breeding. This paper provides an overview and analysis of African crops that have made significant contributions to the United States and globally, and/or hold potential in the 21st century. The paper specifically discusses watermelon, coffee, kola, rooibos, oil palm, shea, cowpea, leafy greens, okra, yam, sorghum, pearl millet, finger millet, teff, and fonio. The review focuses on the intersection of these crops with racialized peoples, with a particular focus on African-Americans starting with slavery. The analysis includes the historical migration of these crops out of African centers of origin, their sociocultural contributions to cuisines and products around the world, their uses today, and the indigenous knowledge associated with traditional cultivation and landrace selection. The untapped potential of local genetic resources and indigenous agronomic strategies are also described. The review demonstrates that African crops played an important role in the development of American cuisine, beverages and household products. Many of these crops are nutritious, high value and stress tolerant. The paper concludes that African crops hold significant promise in improving the resiliency of global food production systems, to mitigate climate change and alleviate food insecurity and rural poverty, especially in dry regions of the world. It is hoped that this review contributes to teaching the next generation of agriculturalists, food scientists and international development professionals about the valuable contributions of Africa’s resilient crops and peoples.